A rare case presentation of large mucinous ovarian cystadenocarcinoma in a young female - Singh, Akansha; Dadhwal, Ankita; Verma, Ashok; Agarwal, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Here authors report a case of large ovarian mucinous cystadenocarcinoma in a young female complicating young pregnancy. Ovarian mucinous adenocarcinoma is a rare ovarian tumour that arises from the surface epithelium of the ovary. A 25-year young female, 9 days post-partum presented to the hospital with complain of abdominal distension. USG finding suggesting large solid cystic mass 36 × 14 cm arising from pelvis extending up to epigastrium. MRI pelvis evident of heterogenous hyperintense solid cystic mass lesion giving bunch of grapes appearance with size 24.5 × 25 × 11.5 cms seen in intra peritoneal space extending cranially up to epigastrium and caudally into pelvis giving anterior displacement of uterus. And posterior displacement of bowel loops. A large part of lesion is cystic with solid component with multiple internal echoes.